Modulation of Cerebellar-Cortical Connectivity Induced by Modafinil and Its Relationship With Receptor and Transporter Expression - Delli Pizzi, Stefano; Tomaiuolo, Federica; Ferretti, Antonio; Bubbico, Giovanna; Onofrj, Valeria; Della Penna, Stefania; Sestieri, Carlo; Sensi, Stefano L (Biological psychiatry. Cognitive neuroscience and neuroimaging, 2025)
BACKGROUND: Modafinil is primarily used to treat narcolepsy but is also used as an off-label cognitive enhancer. Functional magnetic resonance imaging studies indicate that modafinil modulates the connectivity of neocortical networks primarily involved in attention and executive functions. However, much less is known about the drug's effects on subcortical structures. Following preliminary findings, we evaluated modafinil's activity on the connectivity of distinct cerebellar regions with the neocortex. We assessed the spatial relationship of these effects with the expression of neurotransmitter receptors/transporters. METHODS: Patterns of resting-state functional magnetic resonance imaging connectivity were estimated in 50 participants from scans acquired pre- and postadministration of a single (100 mg) dose of modafinil (n = 25) or placebo (n = 25). Using specific cerebellar regions as seeds for voxelwise analyses, we examined modafinil's modulation of cerebellar-neocortical connectivity. Next, we conducted a quantitative evaluation of the spatial overlap between the modulation of cerebellar-neocortical connectivity and the expression of neurotransmitter receptors/transporters obtained by publicly available databases. RESULTS: Modafinil increased the connectivity of crus I and vermis IX with prefrontal regions. Crus I connectivity changes were associated with the expression of dopaminergic D2 receptors. The vermis I-II showed enhanced coupling with the dorsal anterior cingulate cortex and matched the expression of histaminergic H3 receptors. The vermis VII-VIII displayed increased connectivity with the visual cortex, an activity associated with dopaminergic and histaminergic neurotransmission. CONCLUSIONS: Our study reveals modafinil's modulatory effects on cerebellar-neocortical connectivity. The modulation mainly involves crus I and the vermis and spatially overlaps the distribution of dopaminergic and histaminergic receptors.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Cerebellum; Humans; modafinil; neokortex; Neocortex; Female; mladý dospělý; dospělí; stimulancia; lidé; Adult; nervové dráhy; ženské pohlaví; Neural Pathways; Male; Young Adult; mozeček; Modafinil; mužské pohlaví; Wakefulness-Promoting Agents